Implementasi Oral Care Hygiene untuk Mengurangi Risiko Ventilator Associated Pneumonia (VAP) di Ruang Intensive Care Unit (ICU) Rumah Sakit Prof. Dr. Margono Soekarjo: Case Study - Nur Rizky Amalia Shidiq; Sidik Awaludin; Aji Kurniawan (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Background. The insertion of an Endotracheal Tube (ETT) can trigger the occurrence of Ventilator Associated Pneumonia (VAP) due to bacterial colonization of secretions in the oral or tracheal area of ​​the patient. One of the prevention of VAP can be in the form of providing oral hygiene in intubated patients. The purpose of the implementation is to find out the application of the use of oral hygiene guidelines from the Beck Oral Assessment Scale (BOAS) in intubated patients in the ICU Room of Prof. Hospital. Dr. Margono Soekarjo Method. Implementation was carried out using a case study method with a total of 10 patients divided into 2 groups. Both groups were assessed for BOAS at the time the patients were intubated and extubated. Evaluation was carried out using the Mucosal-Plaque Score (MPS). Results. Characteristics of respondents have an age range of 37-66 years. It is known that the average difference in the decrease in BOAS scores is the intervention group. While the MPS Score in the two groups did not have a difference. Conclusion. Oral care hygiene with the guidance of the Beck Oral Assessment Scale (BOAS) can be used to reduce the risk of Ventilator Associated Pneumonia (VAP) in intubated patients.